Forecasting of onion (Allium cepa) price and volatility movements using ARIMAX-GARCH and DCC models - Ghosh, Sourav; Singh, K N; Thangasamy, A; Datta, Debarati; Lama, Achal (The Indian Journal of Agricultural Sciences, 2020)
In the present investigation an attempt has been made to forecast and understand the volatility transmission in onion prices for three vital markets in Maharashtra, viz. Lasalgaon, Pune and Nagpur. The ARIMAX-GARCH model was employed to estimate mean and volatility among the different markets and also examined the nature of dynamic correlation using the DCC model. The quantity arrival of each market was considered as covariate to improve the mean forecast. We have obtained superior results for ARIMAX-GARCH over ARIMAX model in terms of forecasting. Forecasting efficiency of the models was judged in terms of lower RMSE and MAPE values. Presence of volatility was found in and between the markets as well. Lasalgaon market exhibits highest volatility, whereas the combination of Lasalgaon and Nagpur market experiences the largest volatility movement among them. Identification of interdependency of the markets in terms of volatility movement helps the traders as well as policy makers in a large way. The concerned stakeholders can easily anticipate the prices of other dependent market based on the behaviour of one market.